Measurement and Correlation of Partition Coefficients of Glycyrrhizic in Aqueous Two-phase EOPO/K2HPO4 Systems - HUO, QING; LIN, QIANG; GAO, WEI; LI, HAIXIA (Asian Journal of Chemistry, 2010)
The partition behaviour of glycyrrhizic ammonium salt in ethylene oxide-propylene oxide random copolymer (EOPO)/K2HPO4/water systems was investigated. The optimum conditions were EOPO L64 28 %, K2HPO4 32 %, phase separation temperature was 63 ºC, yield of glycyrrhizic ammonium salt could reach 68.4 %. Based on the modified model ln K/R = A* + b*(w" - w') + c*(w" - w')2, partition coefficients of glycyrrhizic in aqueous two-phase extraction system of EOPO/ K2HPO4 aqueous two-phase systems were correlated. It was found that the correlation of the experimental data was quite satisfactory.